Penerapan Model CTL dengan Menggunakan Media Wayang Kulit untuk Meningkatkan Karakter Siswa SDN 02 Winongo Manguharjo Kota Madiun. - Prasetyowati, Etik; Malawi, Ibadulah; Rifa’i, Muhammad; Hanif, Muhammad (Wewarah: Jurnal Pendidikan Multidisipliner, 2024)
The aim of this research is to increase the character values of honesty and helpfulness in class IV students in science subjects at SDN 02 Winongo, Manguharjo District, Madiun City in 2023/2024. This research uses a qualitative approach with the type of classroom action research. This action research was carried out in three cycles. Data was collected through tests, observations, interviews and documentation. The data analysis technique in this research is qualitative data analysis.  The data obtained for each cycle is in the form of student activity data and student character assessment data in science learning using the CTL method and shadow puppet media. The research results showed that the use of the CTL method with shadow puppet media can increase the character values of honesty and helpfulness.  This was proven in the first cycle, the average honesty character value was only 62.90, increasing by 17.54% in the second cycle to 73.93. However, this did not meet the KKM 75, so it was continued in cycle III until finally there was an increase of 38.08% to 86.85 for the average honesty character score. Meanwhile, the helpful character in the initial test of cycle I reached an average score of 65.33 and increased by 14.08% to 74.53. Because it had not yet reached the KKM standard, it was continued to cycle III and the results increased 33.02% to 86.90 for the average value of helpfulness.